USE OF MODIFIED BITUMEN BY LIGNIN AND WASTE PLASTIC IN BITUMINOUS CONCRETE - Dubey, Vaibhav; Parihar, Satish (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The advancement of the country's transport infrastructure is a key factor in the growth of a country. Since India uses flexible pavement often, measures must be done to prolong the life of bituminous pavements. Due to repetitive traffic loads, flexible pavement is frequently vulnerable to issues including rutting, cracking, and other failures and emits significant amounts of CO2, CH4, and N2O. In this project, we have substituted lignin and plastic waste for bitumen in the amounts of 2 & 2%, 4 & 4%, 6 & 6%, 8 & 8%, 10 & 10%, and 12 & 12%, respectively. A number of tests, including those for penetration, ductility, softening point, flash & fire point, and Marshall Stability test, have shown that waste materials like lignin and plastic can act as a binding material for asphalt, improving its properties and helping to reduce CO2, CH4, and 2 omissions. When compared to other proportions employed, it is discovered that the mix percentage of 8 & 8% produces effective outcomes.